Leprechauns don't play basketball - Dadey, Debbie; Gurney, John Steven, 1962-; Jones, Marcia Thornton (New York : Scholastic, 1992)
There are some pretty weird grown-ups living in Bailey City. But could a very short basketball coach from Ireland really be a leprechaun? The Bailey School kids are going to find out.
"A little apple paperback.".
3.9
3-6
Keywords: Leprechauns -- Fiction; Schools -- Fiction; Leprechauns -- Fiction; School stories